Café Betterfield: Optimising the food menu - ANG, Marcus (Institutional Knowledge at Singapore Management University, 2018)
John Chow, the owner of Café Betterfield (CBF), is a food gourmet and a passionate entrepreneur. CBF offers a wide spread of food options, and this was a big draw for many of its regular customers. With these strengths, Chow was puzzled by the lacklustre and irregular profitability of the cafe. Mandy Lim, the newly-hired manager of CBF, was tasked to investigate and find solutions to the current problems. The case reinforces the students’ skills in data processing, problem analysis, and numerical computation. Concepts and techniques covered include spreadsheet modelling, optimisation, and post-optimality analysis. Students will understand the impact of service design on the efficiency of operations, understand the trade-off between operational efficiency and divergence of services and be able to implement the Kasavana & Smith Matrix to optimise the food menu.